Immunotherapy Induced Myasthenic-Like Syndrome in a Metastatic Melanoma Patient With Amyotrophic Lateral Sclerosis. (December 2020) - Jaffer, Muhammad; Chung, Matthew; Sharda, Esha; Ramsakal, Asha; Peguero, Edwin; Verma, Neha; Mokhtari, Sepideh
Immunotherapy agents such as ipilimumab and nivolumab are immensely effective in the treatment of various malignancies. Despite this, neurologic immune-related sequelae (NIRS) have been observed. Prompt diagnosis and treatment is critical to improve patient outcomes. We present a case of a 63-year-old man with stage IV metastatic melanoma beginning treatment with ipilimumab and nivolumab. Gathered history from the patient showed that he had a 3-year presentation of bradykinesia, shuffling gait, and muscle cramping. After one dose, the patient began to have progressively worsening generalized weakness; after receiving the immunotherapy, there was a rapid decline in his health. In addition to weakness, the patient developed diplopia, impaired single breath count, lingual and upper/lower extremity fasciculations, and brisk reflexes. While the lumbar puncture and myasthenia panel were non-diagnostic, the electromyography (EMG) revealed axonal neuropathy and diffuse denervation/reinnervation changes. Furthermore, a magnetic resonance imaging (MRI) displayed fatty replacement of the tongue with a bright tongue sign. These results pointed to the diagnosis of amyotrophic lateral sclerosis (ALS) superimposed onto myasthenic-like syndrome. The patient was started on various treatments; however, unfortunately he died due to acute hypoxic respiratory failure. This case highlights important considerations that must be taken when using immunotherapy, especially in patients with pre-existing neurological deficits. Furthermore, it shows the importance of early diagnosis as treatment can potentially cure adverse sequelae.